Failed Emancipations: Youth Transitions, Migration and the Future in Morocco - Carles Feixa; José Sánchez-García; Celia Premat; Nele Hansen (Societies, 2022)
Several authors have highlighted the importance of marriage as a social marker that alters the social categorization of individuals and their relationships from youth to adulthood, according to the cultural construction of the life course in Arab countries. This article analyzes the interaction between the socio-political framework (structure) and the capacity for individual action (agency) in the context of biographical experiences for achieving emancipation in Morocco. This perspective responds to different authors’ demands to include young people’s subjective approaches in the analysis process. This study is guided by the following questions: What capacity do young Arabs have to decide the orientation of their life trajectories? Which factors (cultural, family, socioeconomic, educational, etc.) generate young people’s expectations regarding their transition to adult life? What are the social constrictions that lead to failure in the emancipation process, according to Arab societies?